Kritik Satire pada Pejabat Negara Indonesia melalui Roasting Stand-Up Comedy Kiky Saputri di Youtube - Dina Safira Putri; Zainal Abidin Achmad; Syifa Syarifah Alamiyah; Heidy Arviani; Roziana Febrianita (Universitas Merdeka Malang, 2022)
The roasting technique is a joke that aims to comment on or criticize people in an entertaining style. This study aims to analyze the delivery of criticism through the roasting of stand-up comedian Kiky Saputri to state officials. This qualitative research method uses virtual ethnographic approach by conducting virtual interviews with six informants. The researchers were participatively involved through the comment’s column on the YouTube account of Stand-Up Kompas TV and BUMN Muda. This research found that Kiky's courage to roast state officials in the form of satire criticism without camouflage, meaning openly mentioning names, events, and actual cases. This research concludes that the courage to roast with a satire criticism style is based on honesty in facts. The dictions avoid blasphemy, sarcasm, and insults. The satire criticism as a tool for evaluating the performance of Indonesian state officials and as a means of political educationKeywords: Roasting, Satire Criticism, Stand-Up Comedy, Virtual Ethnography